Strengthening the Capability of a micro-scale Bag Producer “Katbag” through Business Planning and Digital Marketing - Nurqamarani, Adisthy Shabrina; Fadilla, Sarah; Thaha, Abdurrahman Rahim; Juliana, Ari; Ulfa, Cherly Kemala; Rachmawati, Dwi; Kuncoro, Setyo; Priyanto, Agus; Santosa, Agus (Engagement: Jurnal Pengabdian Kepada Masyarakat, 2024)
Micro businesses play a crucial role in Indonesia's economy. Their significance in economic recovery is underscored by their substantial contribution to the labor sector. The community engagement partner, "Katbag," specializes in the production of bags and accessories, also souvenir and corporate merchandise. Partnering with Katbag was motivated by the competitiveness of its offerings and high entrepreneurial drive. However, despite their product excellence, Katbag faces challenges and limitations, particularly in business administration, HR, and marketing. This program aims to assist in enhancing the partner's capacity in terms of business planning and digital marketing so that they can develop their business further. The method involves planning, implementation (training in digital marketing and business administration), along with rigorous monitoring and evaluation. After participating on the program, the partner has gained knowledge in business administration and website management to build digital presence and reach more consumers online.